Youth Empowerment of St. Stefanus Holima (OMK) Catholic Church Through the Processing and Packaging of Sweet Potato Chips (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Sweet potatoes in the Papuan Mountains region are very abundant and are sold without any processed variations. It is not uncommon for sweet potatoes to not sell even though the price is relatively cheap and affordable for all levels of society. For this reason, community service activities are carried out through community empowerment in implementing technology for processing and packaging sweet potato chips. The aim of this activity is to provide education to church youth (OMK) in Isakusa village to support increasing the income of church youth, and to support government programs in the agricultural sector. The method of implementing activities starts from determining the location, scheduling, socialization, making chips, and packaging the chips. The results of the training on processing and packaging sweet potato chips received a good response from the young people of St. Catholic Church (OMK). Stefanus Holima Wamena because during training it is not uncommon for the youth involved to show facial expressions that are curious, interested, happy and full of enthusiasm. Some of them said that they were very happy and satisfied with the products they had made and felt motivated to make them independently to sell to local people and local and foreign tourists as a form of home business that could increase their income. They also said that if possible, this kind of activity would be carried out sustainably by processing various types of basic materials which are superior in Wamena in particular and Mountain Papua in general.